Postdigitale Jugendkulturen - Zu neuen Formen der Biographisierung - Jörissen, Benjamin; Engel, Juliane; Schreiber, Jakob (Zeitschrift für Pädagogik / Beiheft, 2024)
This article discusses the epistemologica! potential of post-digital and media- theoretical approaches to differentiate forms of biographisation in the context of biographical youth culture research. To this end, it reflects on the concept of biography in qualitative research as a Euro- and subject-centred concept and shows how this is increasingly coming into friction with global, cultural and social transformation phenomena such as digital change. Based on this, a relational conception of biographisation can be developed from a media theory perspective, which embeds it in socio-technological contexts. Finally, selected examples are used to present empirical points of connection for biography-orientated youth research.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Biographical Research; Biography; Post-digital; Software Studies; Youth Culture